Liquid biopsy in whole blood for identification of gene expression patterns (mRNA and miRNA) associated with recurrence of glioblastoma WHO CNS grade 4 - Muhtadi, Razan; Bernhardt, Denise; Multhoff, Gabriele; Hönikl, Lisa; Combs, Stephanie E.; Krieg, Sandro; Gempt, Jens; Meyer, Bernhard; Barsegian, Vahé; Lindemann, Monika; Kasper, Mandy; Stewart, Samantha; et al. (Cancers, 2024)
GBM WHO CNS Grade 4 represents a major challenge for oncology due to its aggressive behavior. Conventional imaging has restrictions in detecting tumor recurrence. This prospective study aims to identify gene-based biomarkers in whole blood instead of isolating exosomes for the early detection of tumor recurrence. Blood samples (n = 33) were collected from seven GBM patients at time points before and after surgery as well as upon tumor recurrence. Four tumor tissue samples were assessed in parallel. Next-generation sequencing (NGS), including mRNA-seq and small RNA-seq, was used to analyze gene expression profiles in blood samples and tumor tissues. A novel filtering pipeline was invented to narrow down potential candidate genes. In total, between 6-93 mRNA and 1-19 small RNA candidates could be identified among the seven patients. The overlap of genes between the patients was minimal, indicating significant inter-individual variance among GBM patients. In summary, this prospective study supports the applicability of gene expression measurements in whole blood for the detection of tumor recurrence. It might provide an alternative to the challenging workflow of liquid biopsy after laborious exosome isolation from whole blood.
Online veröffentlicht: 26. Juni 2024
Gesehen am 30.01.2025